Shared Decision Making with Aboriginal Women Facing Health Decisions: A qualitative study identifying needs, supports, and barriers. (December 2015) - Jull, Janet; Giles, Audrey; Boyer, Yvonne; Lodge, Minwaashin; Stacey, Dawn
Shared decision making (SDM) may narrow health equity gaps by engaging clients with their health care providers in decision making; little is known about SDM interventions with Aboriginal people. This study describes the health decision-making experiences of Aboriginal women by identifying decision needs, supports, and barriers. An interpretive descriptive qualitative study was conducted from January to June 2013 with an advisory group using a mutually developed ethical framework, participatory research principles, and postcolonial theory. Aboriginal women at Minwaashin Lodge were interviewed in semi-structured interviews and transcripts were coded using thematic analysis. Participants were 13 women between 20 and 70 years of age, and of Inuit, Métis, or First Nations descent. SDM needs and supports are represented by themes focused on relational features of SDM, and presented in a Medicine Wheel framework. Findings indicate that to be relevant for Aboriginal women, SDM tools and approaches may need to be adapted, and participatory approaches must be used.